Establishing an evidence base for adapting social housing for an ageing population. Issue 2 (1st August 2016) - Boyle, Frank; Thomson, Craig
Abstract : Purpose: Prolonged life expectancy coupled with the retirement of the "post war baby boomers" has resulted in an exponential rise in the 50+ population, peaking in the UK in 2035. Recognising that longevity is often not accompanied by health, mobility or quality of life, the "shifting the balance of care" agenda promotes an integrated care model based around the resident's home. This study aims to explore the adaptability of the existing social housing stock and how it relates to the requirements and preferences of the ageing population. Design/methodology/approach: This research focuses at the local authority level, with the lead author embedded within North Ayrshire Council to establish the evidence base for their housing strategy for older people. Following a constructivist grounded theory approach, key themes emerge through consultation with a working group, wider stakeholder groups and an iterative review of policy and literature. These themes were explored through an evidence base of available health and housing datasets, and a questionnaire survey of 1, 500+ people aged 50+ exploring housing preferences and needs for older people; six focus groups split between residents and social housing providers and stakeholder interviews. Findings: The scale and acute nature of the problem facing social housing providers is highlighted and reveals an alarming information gap within housing data sets, exposing an in-balance between the supply and demand and realising the cost implications for adapting the housing stock. Practical implications: It is important to resolve this information gap to develop the social housing stock to respond to preferences and establish solutions appropriate for its residents. Originality/value: This work strengthens calls for a cohesive and integrated housing, health and social care system and exposes the challenge of delivering this at a local authority level.